2014
DOI: 10.1186/2008-6970-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dietary vitamin E against fungicide copperoxychloride stress on Nile tilapia, Oreochromis niloticus (L.), fingerlings

Abstract: A 2 9 3 factorial experiment was designed to study the effect of sublethal toxicity of technical grade copperoxychloride, dietary vitamin E and their interactions on growth performance, some blood parameters, DNA fragmentation and histopathological lesions of Nile tilapia (Oreochromis niloticus). The 96 h LC 50 of copperoxychloride was found to be 129.21 mg/l. Four hundred and fifty fingerlings with an average initial body weight ranged from 1.92 to 2.04 ± 0.11 g were randomly distributed equally in six treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Meanwhile, in other analysed variants (even in the unsupplemented control group) slight changes were noted in these organs including degeneration congestion in the blood sinusoids of hepatocytes and degeneration in the hypodermis layer and villi, which often occurs after feeding of high‐soybean diets or in intensive fish‐farming conditions. This results are in agreement with Hassaan et al (), who reported that liver of Nile tilapia fed control diets which contained high portion of soybean meal was normal architecture, only some samples showed fatty degeneration. A histological analysis of the liver of sea bass fed different levels of yeast extract showed steatosis with fat degeneration, whereas liver morphology was considerably improved with yeast extract supplementation (Panagiotidou et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, in other analysed variants (even in the unsupplemented control group) slight changes were noted in these organs including degeneration congestion in the blood sinusoids of hepatocytes and degeneration in the hypodermis layer and villi, which often occurs after feeding of high‐soybean diets or in intensive fish‐farming conditions. This results are in agreement with Hassaan et al (), who reported that liver of Nile tilapia fed control diets which contained high portion of soybean meal was normal architecture, only some samples showed fatty degeneration. A histological analysis of the liver of sea bass fed different levels of yeast extract showed steatosis with fat degeneration, whereas liver morphology was considerably improved with yeast extract supplementation (Panagiotidou et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…Total alkalinity and chloride were monitored twice weekly by titration; pH was monitored twice weekly using a pH meter (Orion pH meter, Abilene, Texas, USA). All tested water quality criteria (temperature, DO, pH, total ammonia and nitrite) were estimated according to standard methods as described elsewhere (Hassaan, Goda, Mahmoud, & Tayel, ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the powerful modulatory effects of vitamin E was demonstrated against atrazine-induced toxicity in rats (Singh et al, 2011), in the catfish Clarias gariepinus (Kadry et al, 2012), in the freshwater shrimp Palaemonetes argentines (Griboff et al, 2014) and against the geno-and cytotoxicity of Cd, Cu, Pb and Zn in erythrocytes of O. niloticus (Harabawy and Mosleh, 2014). Recently, Hassaan et al (2014) showed that many cytotoxic and genotoxic alterations induced in O. niloticus by exposure to the fungicide copper oxychloride, were reversed to a great extent with supplementation of vitamin E in diets, in comparison with those exposed to fungicide alone. Other studies document the potential protection of vitamin E against the oxidative stress induced by metals, herbicides and oxidized fish oils in mice and fish (Al-Attar, 2011;Gao et al, 2014).…”
Section: Fig 2 Superoxide Dismutase (Sod) (A) and Catalase (Cat) (Bmentioning
confidence: 96%
“…Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are liver enzymes and they have the function of transferring the amino group from alpha-amino acids to alpha-keto acids. A large amount of ALT and AST is released in the blood mostly during liver cell damage [53]. Thus, detection of the serum level of ALT and AST allows monitoring liver cell damage.…”
Section: Hematological Analysis and Biochemical Bloodmentioning
confidence: 99%